Surface Laser Quenching as an Alternative Method for Conventional Quenching and Tempering Treatment of 1538 MV Steel - R. Carrera-Espinoza; A. Rojo Valerio; J. del Prado Villasana; J. A. Yescas Hernández; P. Moreno-Garibaldi; M. A. Cruz-Gómez; U. Figueroa López (Advances in Materials Science and Engineering)
This paper aims at encouraging the use of laser treatment as an environmentally friendly technique to improve the mechanical properties of metallic materials over conventional quenching and tempering techniques through the study of the tribological behavior of AISI 1538 MV steel subjected to surface laser quenching treatment. Sliding wear tests were carried out by the pin-on-disk method. In order to identify the wear mechanisms, the worn surfaces on the disks were evaluated by scanning electron microscopy and the wear scars on the ball were observed by optical microscopy. Results reveal that laser treatment reduces the average friction coefficient by 25% and the wear rate by 60% compared with those achieved by the conventional methods, while the depths of the wear track and hardness of the cross section and surface are maintained.